The potential of blue-green infrastructure in spatial revitalization – application in Municipal Revitalization Programs - Cichocki, Michał; Chruściel, Klaudia (Studia z Polityki Publicznej, 2024)
Opposing the spatial degeneration of cities requires a wide range of efforts which combine, among others, activities related to blue and green infrastructure (BGI). This paper examines the scope and manner of using BGI to revitalise space in municipal revitalisation programmes (MRP). In the first part of the study, the theoretical framework for the studied issues has been outlined based on subject literature. The manner of understanding BGI and revitalisation in the current legal system has been defined. The analysis covered 60 MRPs from 2016 to 2021 in accordance with the methodology set out in the second part of the study, based on how often BGI appeared in key MRP sections such as in-depth diagnosis of revitalisation area, the objectives and directions of the process, and the revitalisation projects. The last part of the paper describes the results of analysis and their evaluation. One of the main conclusions of the work we conducted is that BGI elements appear quite frequently in revitalisation programmes; however, their full potential remains untapped. The projects carried out in the studied area have rarely had the form of complex urban projects. The main method of using BGI in MRPs is currently the technical dimension that focuses on improving the quality of existing resources. To a lesser extent, revitalisation projects that use the BGI concept are reflected in the social and occasionally in the natural dimension.